Analisis Perkembangan Wisata Halal dan Dampaknya terhadap Ekonomi Korea Selatan pada Tahun 2019-2021 - Putri, Tantry Hardiansal (Universitas Bosowa, 2025)
The development of halal tourism in South Korea has been a focal point for the government and relevant institutions since the early 2010s. South Korea took strategic measures to enhance accessibility and services for Muslim tourists visiting the country. Since the launch of the